Faculty Reflections About Participating in International Medical School Curriculum Development, a Qualitative Study - Amar Kohli; Russell Schuh; Margaret McDonald; Ana Arita; David Michael Elnicki (International Medical Education)
Nazarbayev University School of Medicine selected the University of Pittsburgh School of Medicine to guide their curricular development. University of Pittsburgh faculty members teaching in the medical school were asked to help develop the curriculum in Nazarbayev. Some were asked to travel to Nazarbayev University to provide mentoring. Realizing that this would be a new activity, we wanted to investigate the perceived motivations, rewards, and barriers to participation. We conducted open-ended interviews of University of Pittsburgh faculty members, who were asked to participate in a project about motivations for accepting or rejecting the offer. We asked those accepting about the benefits and negatives. Nineteen faculty members agreed to 30 min interviews, which were digitally recorded and transcribed. All interviews were coded. Participating faculty members felt that reviewing their courses improved them. Most noted increased altruism and felt improved as educators. Some felt angst in providing their curricula. Several felt that traveling was challenging, but video conferencing technologies facilitated communication. Interviewees desired tangible rewards. This study highlights faculty perceptions of international curricular development. Faculty members felt that rewards included an improved native curriculum and personal and professional enrichment. Time constraints and distance were the main challenges and the primary reason others declined. The faculty perceived multiple benefits from this curricular development and collaboration. More transparency regarding expectations and the degree of assistance Nazarbayev University needed may have assuaged these fears.